Determinants of community perception on food technology-based shallot waste management for nutritional security: a cross-sectional study - D. Yan El Rizal Unzilatirrizqi; Riska Arsita Harnawati (Intelektual Pustaka Media Utama, 2026)
Shallot production in Indonesia, particularly in Brebes Regency, generates substantial agricultural by-product waste that poses significant environmental and public health risks due to inadequate community-level management. This cross-sectional quantitative study investigated the influence of government role, infrastructure availability, and public knowledge on perceptions of shallot by-product waste management among 180 respondents selected through proportional random sampling. Data were collected using structured Likert-scale questionnaires and analyzed through multiple linear regression, Spearman's rank correlation, and gap analysis. Gap analysis revealed critical deficiencies in public knowledge (50.6-76.1%) and infrastructure (69.2%), despite universally positive perceptions toward waste management. Multiple linear regression demonstrated that government role (β = 0.342, p < 0.001), infrastructure availability (β = 0.298, p < 0.001), and public knowledge (β = 0.152, p = 0.007) significantly predicted waste management perceptions, collectively explaining 37.8% of the variance (Adj. R² = 0.378). The government's role contributed the largest effective contribution at 18.74%. These findings carry substantial public health implications, as improved waste management can reduce disease vectors, minimize environmental contamination, and enable by-product valorization for nutritional supplementation. The study recommends strengthening government intervention, expanding waste infrastructure, and enhancing community health literacy as integrated policy strategies to optimize agricultural by-product management and safeguard community nutritional well-being in shallot production centers.